Complete genome sequencing and analyzing the genes of pseudomonas SP. BIOMIG1BAC - Altınbağ, Recep Can. (Thesis (M.S.) - Bogazici University. Institute of Environmental Sciences, 2021., 2021)
Disinfectant consumption has increased with the pandemic of SARS-CoV-2. Benzalkonium chlorides (BACs), which are a group of quaternary ammonium compounds (QACs), are widely used as active ingredients in many of those disinfectants in the market. Previously, a strain of Pseudomonas, i.e. BIOMIG1BAC, that can completely mineralize BACs was isolated, and its draft genome was sequenced. Moreover, the oxyBAC, which is the key gene in the biotransformation of BACs, was identified and verified through genetic experiments. The main objective of this research was to understand the ecological significance of the strain BIOMIG1 and its oxyBAC gene at genomic level. The complete genome of the Pseudomonas sp. BIOMIG1BAC was obtained with a hybrid method that combines Illumina short-read sequencing and Oxford Nanopore long-read sequencing technologies. Pseudomonas sp. BIOMIG1BAC has a genome composed of a single circular chromosome with a 7,675,262 bp length. Phylogenomic analysis showed that the strain BIOMIG1BAC is a new species classified under Pseudomonas protegens subgroup, which is tentatively named as Pseudomonas alexanderii sp. nov. The key genes of the BAC biodegradation pathway, including oxyBAC, are associated with transposons therefore they can be horizontally transferred among bacteria. Two transposon motifs that carry the oxyBAC and its accompanying genes, were identified in the oxyBAC containing genomes of other (QAC degrading) microorganisms. The outcomes of this study suggest that oxyBAC is present in phylogenetically diverse group of bacteria and has a potential to horizontally transfer within bacteria via transposition to plasmids and phage genomes in communities under the stress of disinfectants.
Keywords: Pseudomonas.; Benzalkonium chloride.